Influence of orthodontic treatment on periodont (literature review) - Borysenko, А. В.; Batig, І. В.; Kuzniak, Н. Б.; Batig, В. М. (Actual Dentistry, 2022)
Summary. Today, the need for orthodontic treatment of anomalies of tooth position and occlusion is constantly growing. In the practice of orthodontics use a variety of orthodontic appliances. The most widely used non-removable appliances that allow treatment of adult patients. However, dentists often intensify orthodontic appliances to speed up the end of treatment result. Unfortunately, this has a very adverse effect on periodontal tissues. This article analyzes the data of the dental literature on the impact of orthodontic treatment on the hard tissues of the teeth and, especially, on the periodontium. The main factors of periodontal damage during orthodontic treatment are determined. An analysis of possible areas of prevention of periodontal disease during orthodontic treatment was presented.